Monitoring of long-term treatment with acitretin in prepubertal age. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
The available data refer mainly to etretinate. However, since in the organism etretinate is converted into acitretin, these data are also valid for treatment with acitretin (Neotigason®). The side effects of retinoids are well-known by dermatologists.This is why they are only mentioned in Table 1. Here we are talking about the side effects on the bone metabolism in case of long-term treatments in children and adolescents, as necessary in the treatment of some genetic skin disorders in order to allow the life of the patient, for instance in harlequin ichthyosis, or to make the quality of life more satisfactory in some severe forms of ichthyosis and erythrokeratodermas. In the latter case the indication to the treatment with acitretin should be advised after careful consideration of the risk/benefit ratio in every single case, taking into account that, especially in adolescent age, when a treatment with acitretin is started and it is responsible for a significant improvement, it is very difficult to withdraw or reduce the dose of the drug.